Sustained release polyurethane microcapsules by interfacial polycondensation using aromatic diols - Yadav, Prashant; Ravikumar, Aniruddha; Ambade, V. Ashootosh; Shanmuganathan, Kadhiravan (Reactive & Functional Polymers, 2025)
Polyurea-urethane (PUU) microcapsules prepared via interfacial polymerization have gained significant interest due to their tunable size and membrane thickness, high loading efficiency, and scalability. Although several aromatic and aliphatic diols and polyols have been used to produce PU foams and films, the use of aromatic diols to synthesize PUU MICs via interfacial polymerization is an unexplored domain due to the restricted solubility of aromatic diols in water. This report highlights the successful preparation of PUU microcapsules using an aromatic diol (benzene-1,4-dimethanol, BDM) to encapsulate dimethyl phthalate (DMP), a model insect repellent. The developed PUU microcapsules exhibited a high % encapsulation efficiency of 92 % and a size range of 1-20 mu m. Differential scanning calorimetry (DSC) thermograms revealed a significantly high glass transition temperature (Tg) of 143 degrees C as compared to 108 degrees C in the case of PUU MICs with aliphatic diols. Release studies confirm enhanced barrier properties for aromatic diol-based MICs as compared to aliphatic ethylene glycol-based PUU MICs, and interpretation of the release profile using the Weibull Model reveals that Fickian diffusion is the dominant mechanism in the release of DMP. These microcapsules can be used in high-performance applications such as composites, coatings, electronics, and construction.
Keywords: interfacial polymerization; Microencapsulation; polyurethane; sustained release